A group intervention to reduce smoking in individuals with psychiatric disorder: brief report of a pilot study - Stephen R. Kisely; Mike Wise; Neil Preston; Senia Malmgren; Peter Shannon (Elsevier, 2003)
Abstract Objectives:To evaluate a group intervention to help individuals with psychiatric disorder stop smoking. Method:A waitlist‐treatment crossover design. Outcome measures included smoking cessation, motivation to stop, the Fagerstrom Test for Nicotine Dependence (FTND), urinary cotinine and psychiatric symptoms on the General Health Questionnaire. Results:38 subjects participated, of whom 19 completed the waitlist and intervention phases. There were no significant differences between subjects and dropouts. During the waitlist period there were no significant changes in tobacco use. At the end of the intervention, almost a quarter had stopped smoking, (z= ‐2.24, p=0.02). Subjects also showed significant improvements on state of change, FTND score and urinary cotinine levels. These improvements were maintained at three‐month follow‐up (n=10). Psychiatric morbidity showed no change. Conclusions:It is possible to reduce smoking in individuals with psychiatric disorder. Implications:Larger randomised controlled trials are indicated to determine the relative contributions of nicotine replacement, bupropion and group interventions to smoking cessation in this population.